PENGENALAN KOSAKATA DASAR BAHASA SUWAWA MELALUI MEDIA GAMBAR KEPADA PELAJAR LINGKUNGAN SEKOLAH DI DESA TINGKOHUBU KECAMATAN SUWAWA - Herman Didipu; Salam Salam; Sitti Rachmi Masie; Ikram Tuluki; Kartika Kartika; Lisyan Husain; Nurwafik Azizah; Dewi S. Labuang (LPPM Universitas Bina Bangsa, 2024)
This community service activity is a collaborative activity between lecturers and students of the Department of Indonesian language and literature, Gorontalo State University. This activity was carried out on the basis of concern and concern for the existence of Suwawa language as one of the regional languages in Gorontalo province which began to experience degradation. Several studies have shown that the Suwawa language has begun to decline. For this reason, this activity is a form of conservation and revitalization of the Suwawa language. This service was held in Tingkohubu Village, Suwawa district with participants were children between the ages of 3-8 years. The stages of activities include preparation, implementation, and evaluation. The preparation stages include coordinating with the village government, recruiting participants, to arranging materials and preparing drawing materials. The implementation stage is in the form of giving material using the expository method, guess the picture, and games. The evaluation was conducted to test children's mastery of basic vocabulary of Suwawa language using quiz and door prize methods. The results of this activity showed a significant increase in vocabulary Suwawa language in children. This can be seen from their enthusiasm when answering the quiz to guess the words in the picture